Automated model integration at source code level: An approach to implementing models into the NASA Land Information System. (January 2023) - Wang, Shugong; Kumar, Sujay V.; Mocko, David M.; Arsenault, Kristi R.; Geiger, James V.; Peters-Lidard, Christa D.
Abstract: This paper presents an approach to automated model integration into the NASA Land Information System (LIS). LIS defines interfaces for integrating models, which do not often have standardized coupling interfaces. Additional software development is needed when implementing models. The automated approach simplifies these barriers. LIS standardized modeling interface (LSMI) is proposed as a prerequisite Fortran subroutine, which is directly callable by LIS and calls model physics. Data communication between LIS and a model can be connected through an LSMI. The LSMI arguments can be functionally categorized. Taking their specifications, implementation code can be generated based on code templates with programming logic and language elements incorporated. An Excel/VBA-based tool (LIS-MIT) has been developed for automating LIS model implementation. Since the development of LSMI requires basic skills, LIS-MIT can significantly lower the development difficulties and efforts. The proposed approach can be generalized and applied for integrating models into other modeling environments. Highlights: A general approach has been developed for automating the integration of models into a modeling framework with a set of predefined programming interfaces. A toolkit based on Excel/Visual Basic for Application has been developed for generating source code to implement models into the NASA Land Information System (LIS). Application of the toolkit has significantly reduced programming overhead while ensuring the integrity of model integration.